Incorporating the Shariah-Based Quality Management Standard MS1900:2014 into Cooperatives: Another Growth Strategy? (Journal of Entrepreneurship and Business, 2025)
The Malaysian Standard (MS) 1900:2014 is a Shariah-compliant quality management system integrating universal ethical principles—such as justice, honesty, and discipline—into organizational processes. Endorsed by SIRIM, Malaysia’s standards body, MS 1900:2014 provides a framework for aligning Islamic principles with quality management practices. Since its initial certifications in 2008, adoption has grown steadily, with approximately 40 organizations certified by 2023, though implementation remains limited across Malaysia’s diverse institutional landscape, especially among cooperatives. Utilizing qualitative research methodology, a case study of eight cooperatives from Malaysia’s Top 100 List of 2022 offers insights into how MS 1900:2014 can enhance cooperative growth and performance. Semi-structured interviews were conducted with the Board of Cooperative Directors, Cooperative Managers, and SIRIM Principal Auditor. These findings emphasize the standard's potential not only for quality improvements but also for supporting sustainable economic growth within cooperative sectors. The research contributes to the understanding of quality management systems and their role in integrating Shariah-based principles for enhanced performance, benefiting cooperatives and the broader economy.
Keywords: Array; Array; Array